FOXM1 predicts disease progression in non-muscle invasive bladder cancer - Rinaldetti, Sebastien; Wirtz, Ralph; Worst, Thomas Stefan; Hartmann, Arndt; Breyer, Johannes; Dyrskjot, Lars; Erben, Philipp (Journal of Cancer Research and Clinical Oncology, 2018)
PURPOSE: The proto-oncogene forkhead box M1 (FOXM1) is associated with poor survival in many cancers. The impact of FOXM1 expression on progression-free survival (PFS) of non-muscle invasive bladder cancer (NMIBC) has not yet been investigated. The differential expression of FOXM1 between the different molecular NMIBC subtypes has further been assessed. METHODS: Transcript levels of FOXM1 and MKI67 were determined in 460 NMIBC patients (UROMOL cohort) by RNA-Seq and validated in silico by the Chungbuk and Lund cohort (n = 277). FOXM1 and MKI67 cutoffs were identified by the minimal p value method. Variables were evaluated by multivariable Cox regression analyses in order to identify independent predictors. RESULTS: FOXM1 is an independent predictor for PFS superior to current histological, clinical and molecular staging methods. Patients with high FOXM1 expression have a 6- to 8-fold higher risk of progression in multivariable analysis (p < 0.03). Highest transcript levels were found in the Class 2 and genomically unstable molecular NMIBC subtype (p < 0.03). The proto-oncogene further positively correlated with tumor grade and stage. NMIBCs with high FOXM1 expression showed a PFS advantage when treated with intravesical BCG instillation. CONCLUSION: FOXM1 is a highly prognostic marker for disease progression of NMIBC superior to current histological, clinical and molecular staging methods and MKI67. It is mainly expressed in the Class 2 and genomically unstable molecular bladder cancer subtypes. Its role in drug resistance development makes FOXM1 valuable biomarker for NMIBC risk stratification.
EVALuna2:34602